Ginsan Enhances Humoral Antibody Response to Orally Delivered Antigen - Na, Hee Sam (The Korean Association of Immunologists, 2010)
BACKGROUND: There have been several reports describing the capability of ginseng extracts as an adjuvant. In this study, we tested if ginsan, a polysaccharide extracted from Panax ginseng, was effective in enhancing antibody response to orally delivered Salmonella antigen. METHODS: Ginsan was treated before oral salmonella antigen administration. Salmonella specific antibody was determined by ELISA. mRNA expression was determined by RT-PCR. Cell migration was determined by confocal microscopy and flow cytometry. COX expression was detected by western blot. RESULTS: Ginsan treatment before oral Salmonella antigen delivery significantly increased both secretory and serum antibody production. Ginsan increased the expression of COX in the Peyer's patches. Various genes were screened and we found that CCL3 mRNA expression was increased in the Peyer's patch. Ginsan increased dendritic cells in the Peyer's patch and newly migrated dendritic cells were mostly found in the subepithelial dome region. When COX inhibitors were treated, the expression of CCL3 was reduced. COX inhibitor also antagonized both the migration of dendritic cells and the humoral immune response against oral Salmonella antigen. CONCLUSION: Ginsan effectively enhances the humoral immune response to orally delivered antigen, mediated by CCL3 via COX. Ginsan may serve as a potent vaccine suppliment for oral immunization.